The History of the Development of Cellular Communications (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This article discusses the development of mobile telephone communication systems and the appearance, problems and solutions of systems based on the GSM standard. In 1946, the first radiotelephone communication system was launched in the USA in St. Louis, which was associated with specific difficulties for early mobile communication. Over the years, technical developments, solving problems associated with frequency resources and their limitations, were implemented through the "cell" principle proposed by the American company AT&T. Each cell operated within a limited radius and allowed for the reuse of frequencies. In the middle, in the late 1980s, the GSM standard was introduced. This expanded the capabilities of digital communication technologies, new services and interfaces for mobile subscribers, such as roaming, encryption and identification. The GSM system provided integration with telephone networks and the transition from analog standards to digital standards, which caused various difficulties. The article also provides an overview of the components of the GSM system and their functions, including mobile stations (MS), base stations (BSS) and network subsystem (NSS). The mobile switching center (MSC) provides call control and routing functions, the HLR maintains permanent registration information about mobile subscribers, and the VLR manages temporary location information. This article aims to help users, operators and researchers to further improve the quality of service of mobile communication systems, which are characterized by the expansion and improvement of mobile communication services.